Exercise Interventions and Cardiovascular Health in Childhood Cancer: A Meta-analysis - Morales, Javier S.; Valenzuela, Pedro L.; Herrera-Olivares, Alba M.; Baño-Rodrigo, Antonio; Castillo-García, Adrián; Rincón-Castanedo, Cecilia; Martín-Ruiz, Asunción; San-Juan, Alejandro F.; Fiuza-Luces, Carmen; Lucia, Alejandro (International Journal of Sports Medicine, 2020)
This study analyzed the effects of physical exercise interventions on cardiovascular endpoints in childhood cancer survivors. Relevant articles were systematically searched in PubMed, CINAHL, and Web of Science databases (since inception to 11th September 2019). We performed a meta-analysis (random effects) to determine the mean difference (expressed together with 95% confidence intervals) between pre- and post-intervention values for those cardiovascular endpoints reported in more than three studies. Twenty-seven studies (of which 16 were controlled studies) comprising 697 participants were included. Only three studies reported adverse events related to exercise interventions. Exercise resulted in an increased performance on the 6-minute walk distance test (mean difference=111 m, 95% confidence interval=39–183, p=0.003) and a non-significant trend (mean difference=1.97 ml∙kg−1∙min−1, 95% confidence interval=−0.12–4.06, p=0.065) for improvement in peak oxygen uptake. Furthermore, left ventricular ejection fraction was preserved after exercise interventions (mean difference=0.29%, 95% confidence interval=−1.41–1.99, p=0.738). In summary, exercise interventions might exert a cardioprotective effect in childhood cancer survivors by improving – or attenuating the decline of – physical capacity and cardiovascular function. Further studies, particularly randomized controlled trials, are needed to confirm these benefits.
Keywords: cardiovascular function; exercise is medicine; cardiorespiratory fitness; physical activity; physical capacity; pediatric cancer